Thermal analysis of microchannel heat sink - Mohd Sa'at, Fatimah Al-Zahrah (2006)
Microchannel heat sink is now one of the most effective cooling techniques. As micropump works under pulsation regime and influenced by the possibility of heat transfer enhancement through pulsation, the goal has been to study the effect of pulsation to thermal behavior of microchannel heat sink. A computational model for studying pulsatile flow in microchannel had been developed using FLUENT. The meshes generated had been tested for grid independency and the results numerically iterated by FLUENT had been validated and compared to various published data. The pulsating flow pressure amplitudes were 50%, 70% and 90% of mean pressure and the flow regime is laminar. Pulsation tested was with frequencies in the range 500 Hz to 1.5 kHz. The results of pulsating flow simulations had been analysed and compared with the steady flow simulations. The values of the augmentation factor of heat flux along the flow direction were found to be less than unity. The values of the augmentation factor of heat transfer coefficient along the flow direction were less than unity at the entrance region and increased above unity further downstream. Pulsation had resulted in a lower wall temperature distribution compared to steady flow. The pulsation amplitude and frequency investigated has no significant effect on wall temperature. Heat flux ratio and heat transfer coefficient ratio however varies at frequencies and amplitudes investigated